Exploring Acceptance and Commitment Therapy for parents of preterm infants. Issue 1 (29th February 2020) - Esser, Kayla; Barreira, Lesley; Miller, Doug; Church, Paige; Major, Nathalie; Cohen, Eyal; Orkin, Julia
Abstract: The start of a parenting journey in the neonatal intensive care unit (NICU) presents many stressors to parents. Previous research has shown parents of infants admitted to the NICU experience heightened stress, anxiety, and depression. Mental health support varies across Canadian NICUs with mixed results. One promising intervention that has not been explored in the NICU is Acceptance and Commitment Therapy (ACT), a behavioural therapy that has had positive mental health-related outcomes in similar parental populations. ACT differs from previous mental health interventions such as traditional Cognitive Behavioural Therapy (CBT) as it involves mindfulness and acceptance to increase psychological flexibility. Increased psychological flexibility is linked to greater emotional well-being, a higher quality of life, and decreased stress, anxiety, and depression. There is a need for research investigating the utility of ACT in improving mental health outcomes for parents of preterm infants.